Reduction in Post-transplantation Mortality and Water Requirement of Saplings through Chemical Treatments - Tilak, B. D.; Hanbar, R. D.; Gogte, A. V.; Karve, A. D. (Indian Forester, 1991)
Foliar application of 0.5% aqueous emulsion of HE 110R (mono- and di-ethylene oxide condensation products of technical grade behenyl alcohol) to saplings of forest and fruit trees reduced their post-transplanting mortality and water requirement. It was shown that this treatment caused significant reduction in the rate of transpiration of the plants. Soil application of Jalshakti (a water absorbing carbohydrate polymer) at the rate of 100g per sapling also reduced the water requirement of saplings to the same extent as foliar sprays of HE 110R, but the per ha cost of Jalshakti came to almost 20 times that of HE 110R.